Correlation between Salivary Oxidative Stress Biomarkers and Clinical Severity of Radiation-Induced Oral Mucositis in Head and Neck Cancer Patients - Ayuningtyas, Nurina Febriyanti; Basalamah, Fatimah Fauzi; Brahmanikanya, Gisela Lalita; Mahdani, Fatma Yasmin; Parmadiati, Adiastuti Endah; Radithia, Desiana; Ernawati, Diah Savitri; Shrestha, Madhu; Pasaribu, Ulinta Purwati; Wicaksono, Satutya (European Journal of Dentistry, 2025)
Radiation-induced oral mucositis (RIOM) is the most common side effect of radiotherapy (RT) in head and neck cancer (HNC) patients. Oxidative stress plays a major role in the multistep pathogenesis of RIOM. However, the current understanding of the relationship between salivary biomarkers of oxidative stress and the clinical severity of RIOM remains limited. This study aims to analyze the correlation between salivary oxidative stress biomarkers and the clinical severity of RIOM.This cross-sectional study analyzed the levels of salivary oxidative stress biomarkers from 25 HNC patients who underwent RT using enzyme-linked immunosorbent assay and the clinical grades of RIOM in the cohort. The data were then analyzed using the Spearman's correlation statistical test (p-value < 0.05).The findings demonstrated a significant correlation between salivary glutathione levels (r: –0.396; p: 0.050), superoxide dismutase levels (r: –0.447; p: 0.025), malondialdehyde levels (r: 0.479; p: 0.015), and lactate dehydrogenase levels (r: 0.460; p: 0.025) with the clinical severity of RIOM.The higher salivary oxidative stress correlates with higher severity of RIOM.
Keywords: glutathione; superoxide dismutase; malondialdehyde; lactate dehydrogenase; oral mucositis; saliva; head and neck cancer; radiotherapy